Freedom to Learn in Perspective Al-Quran and Hadith - Rusyaid; Darnanengsih; Triyana (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2022)
This article explains in a simple way related to the freedom of learning offered by the Minister of Research, Technology, and Higher Education and will relate it to the Al-Quran and Hadith. In this study, the author uses the method of library research or library research by using literature related to the concept of self-study from the perspective of Al-Quran and Hadith. While the research approach used is a qualitative approach with descriptive methods. The study results show that the freedom of learning promoted by Nadiem Makarim has been implemented in Islam for a long time. This result is proven by referring to the Al-Quran and Hadith, which is very clear. There are several verses in the Qur'an and Hadith that explain the freedom of learning; each example of this proof is as stated in the Qur'an Surah Al Baqarah verse 31 and Hadith narrated by Bukhari and Muslim.